Alternatives for restoration of a hemisected mandibular molar. (30th July 2014) - Naveen, Y G; Patel, Jayanti R; Parikh, Pooja; Shah, Khyati
Abstract : Hemisection is a common conservative treatment option for periodontally or endodontically compromised teeth. It is most likely to be performed on mandibular molars with class II or III furcation involvement. Their restoration is more critical than implant surgery to ensure the ability to masticate along with the ability to maintain good oral hygiene. There are various alternatives to restore such types of teeth: the remaining root restored as an individual tooth, restoring individual roots with either a molar or premolar morphology using the adjacent tooth as an abutment in a full coverage fixed partial denture, restoring individual roots with either molar or premolar morphology using an inlay type of restoration on the adjacent abutment tooth. This article reports two cases, one treated with molar morphology and an inlay type of restoration and the other with a premolar morphology and a full coverage fixed partial denture.